Precession-band variance missing from East Asian monsoon runoff - S. C. Clemens (Nature Portfolio, 2018)
The underlying mechanisms driving the variability of the East Asia Monsoon during the late Pleistocene remain unclear. Here, the authors present a record of local precipitation and runoff from the East Chain Sea, which indicates strong sensitivity to greenhouse gases and high latitude ice sheet forcing.